Roman Prebujenje - prvenec Zorka Simčiča - Smrdelj, Rok (Slavistična revija, 2015)
The paper deals with the novel Prebujenje (1943), written by the Slovenian writer Zorko Simčič. The main issues addressed in the paper are the question of interpretation of the novel, the question of its role in the Slovenian wartime literature, and the question of its reception. Prebujenje is a bourgeois psychological novel that was conceived as a reaction to the until then prevailing rural narrative prose. The protagonist of the novel is the student Dušan Biljanski who writes humorous short stories and feuilletons and wants to write a great literary work. The main reason that Simčič decided to write the novel was the Finžgar literary award. Although the novel eventually did not receive the award, the publishing house Nova založba nevertheless decided to publish it. The novel has received the Prešeren Award of the city of Ljubljana and has been positively accepted by literary critics. While the novel has not received a literary analysis, it would be incorrect to say that it has been ignored.
Keywords: "Prebujenje"; bourgeois psychological novel; literarna recepcija; literarne študije; literary reception; medvojna književnost; psihološki roman; Simšič, Zorko; Slovene literature; Slovenian wartime literature; slovenska književnost; student novel